Application of Management Accounting Techniques in the Nepalese Manufacturing Firms - Dahal, Rewan Kumar (Nepal Journal of Multidisciplinary Research, 2021)
MA (Management Accounting) data is intended to help users make managerial choices and support organizational activities. This study examined the use of MATs (Management Accounting Techniques) in NMFs (Nepalese Manufacturing Firms) and their progression. The study was based on 291 survey responses of employees from 18 operative listed NMFs. Nineteen MATs were observed in a 5-point Likert scale ranging from 'significantly less' to 'significantly more'. The study's outcomes revealed that the average usage scores of 3.47 (with SD = 0.998) indicated that the NMFs were significantly applying the MATs in their organizational activities and processes. In addition, the moderate user rate of contemporary MATs (45.7 %) was higher than the moderate use rate of traditional MATs (34.5 %), indicating that the NMFs were gradually incorporating the contemporary MATs alongside the traditional MATs. Failure to align appropriate MATs with business processes could lead to managerial misinterpretations. As a result, the study's findings offer a wealth of information and direction to businesses in NMFs.